Application of the Problem-Based Learning Model to Improve the Mathematical Problem-Solving Ability of Class VII Students of SMP Negeri 23 Pekanbaru - Eli Ningsih; Nelli Susanti; Yenni Elifa (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This study aims to enhance students' capacity for solving mathematical problems through a problem-based learning style. One kind of research that is applied is classroom action research. 37 SMP Negeri 23 Pekanbaru grade 7 kids representing a range of academic abilities were used as research participants. Planning, execution, observation, and reflection are divided into two cycles in this study. The gathering of data involved watching teachers and students in action and administering learning achievement exams as part of daily quizzes. The study results suggest that a problem-based learning strategy can improve students' problem-solving abilities. As evidence, the value of learning outcomes rises from cycle I to cycle II. Cycle I and Cycle II students who passed the KKM had success rates of 27.03% and 29.73%, respectively. According to the study's findings, class VII students at SMP Negeri 23 Pekanbaru can improve their arithmetic problem-solving skills and learn more about math by employing a problem-based learning strategy.